Heart rate variability: exploring age, sex & concussion symptoms in youth athletes. Issue 11 (25th May 2017) - Paniccia, Melissa; Lee, Verweel; Taha, Tim; Keightley, Michelle; Thomas, Scott; Reed, Nick
Abstract : Objective: (1) Explore the influence of age, sex on heart rate variability (HRV) in youth athletes; (2) Examine the relationship between baseline/pre-injury concussion symptom domains (physical, cognitive, emotional, fatigue) and HRV Design: Cross-sectional. Setting: Pre-injury/baseline data was obtained from youth athletes across various sports in the Greater Toronto Area. Participants: Youth athletes between 13–18 years of age (N=294), in which females and males were equally represented across age groups. Inclusion criteria: between 13–18 years old, English speaking. Exclusion criteria: developmental and neurological diagnoses. Intervention: Independent variables of interest included demographic factors such as age and sex as well as concussion symptoms. Concussion symptoms were measured using the Post Concussion Symptom Inventory and were stratified by physical, cognitive, fatigue and emotional domains. Outcome measures: Heart rate variability, collected over 24 hours was the main outcome of interest and included time (e.g. SDNN, RMSSD) and frequency domain measures (e.g. HF, Total Power). Variables were logarithmically transformed to increase robustness of linear regression models. Main results: Statistical threshold set at p ≤ 0.05. Significant age effects revealed that older participants displayed higher HRV compared to younger athletes. Significant interaction effect between concussion symptoms and sex on HRV. Cognitive and fatigue symptoms in healthy youth athletes had significant effect on HRV. Conclusions: This study highlights the potential value of a novel neurophysiological indicator used in conjunction with the self-report of symptoms for clinical management. Prospective longitudinal research is needed to further explore the multi-faceted contextual influences of a youth athlete's environment. Competing interests: None.